7*2la puterea1997-6*2 la puterea1996-2*2 la puterea 1998 = 4*3 la puterea1995-3 la puterea1996-3*3 la puterea1994 = 3la puterea 1996-3 la puterea1995-3 la puterea1994-5*9 la puterea 997= 2 la puterea1996+2 la puterea1995+2 la puterea1994-7*4 la puterea997=

1

Răspunsuri

2014-10-24T10:36:23+03:00
A. 7·2^1997 - 6·2^1996 - 2·2^1998 = 2^1996 (14-6-8) = 0
B. 4·3^1995 - 3^1996 - 3^1995 = 3^1995 (4-3-1) = 0
C. 3^1996 - 3^1995 - 3^1994  - 5·3^1994 = 3^1994 (9-3-1-5) =0
D. 2^1996 + 2^1995 + 2^1994 - 7·2^1994 = 2^1994 (4+2+1-7) = 0 ⇒ A=B=C=D
2 5 2